Multidimensionality of Patient-Reported Outcome Measures in Rhinoplasty Satisfaction - Verkest, Valérie; Pingnet, Laura; Fransen, Erik; Declau, Frank (Facial Plastic Surgery, 2022)
The FACE-Q rhinoplasty module (nose and nostrils), Utrecht questionnaire, and Nasal Obstruction Symptom Evaluation (NOSE) scale are validated Dutch patient-reported outcome measures (PROMs) to evaluate rhinoplasty satisfaction. The objective of this study was to analyze the dimensionality of the measured variables in these four existing questionnaires. Additionally, we investigated the ability of the PROMS to measure change. A prospective single-center study was performed in a consecutive cohort of 106 Dutch-speaking patients. Patients were invited to fill in four PROMs: FACE-Q rhinoplasty module (nose and nostrils), Utrecht questionnaire, and NOSE scale, preoperatively and 3 months postoperatively. Item quality was calculated in all four questionnaires. The ability of the questionnaires to differentiate between pre- and postoperative patients was determined with a binary logistic regression. Exploratory factor analysis was performed to determine the latent dimensions. Item quality was confirmed in all questionnaires. Backward binary logistic regression revealed that NOSE and FACE-Q nose module were the best discriminant factors pre- and postoperatively. Combination of these two questionnaires gave a specificity of 97.33% and a sensitivity of 94.52% to discriminate between pre- and postoperative cases. Exploratory factor analysis identified the presence of four dimensions: (1) cosmesis of the nose, (2) cosmesis of the nostrils, (3) nasal function, and (4) psychosocial well-being in rhinoplasty patients. Lack of factorial invariance in the preoperative phase, as compared with the postoperative phase, was detected, especially with the FACE-Q nose and to a lesser extent with the Utrecht questionnaire. The FACE-Q rhinoplasty modules (nose and nostrils), the Utrecht questionnaire, and NOSE scale measure different dimensions of rhinoplasty satisfaction and can be used complementary to each other to obtain a more holistic evaluation of rhinoplasty patients. However, the surgeon should keep in mind that lack of factorial invariance preoperative, as opposed to the postoperative phase, may influence the outcome of these questionnaires.
Keywords: patient-reported outcome measures; rhinoplasty; exploratory factor analysis; patient satisfaction